The impact of wildlife tourism on the foraging ecology and nutritional condition of an apex predator. (December 2019) - Meyer, Lauren; Pethybridge, Heidi; Beckmann, Crystal; Bruce, Barry; Huveneers, Charlie
Abstract: Shark and ray tourism is growing in popularity and often necessitates attractants like bait and chum to encourage close encounters. Such practices remain contentious amongst stakeholders as they may affect the species they target. We used lipid and fatty acid profiles to investigate the effects of South Australia's cage-diving industry on the diet and nutritional condition of white sharks Carcharodon carcharias (n = 75). We found no evidence of dietary shifts or reduced nutritional condition after a >3 week period of tourism-exposed residency at the Neptune Islands where the cage-diving industry operates. White sharks fed on a variety of prey groups, similar to other populations around Southern Australia that are not exposed to ecotourism provisioning. These findings indicate that current cage-diving operations in South Australia do not alter white shark diet and nutritional condition where prey resources are abundant. Graphical abstract: Image 1 Highlights: Previous studies suggest white shark cage-diving changes shark behaviour and daily activity. Lipids and fatty acids in white shark muscle were used to assess the nutritional effects of the cage-diving industry. White shark nutrition is unaffected by practices of the cage-diving industry. White sharks do not consume sufficient bait (tuna) to affect their diet. White sharks foraging ecology at the Neptune Islands is similar to other locations in South Australia.